Aspetti lessicali e semantici nel Quadro comune europeo di riferimento per le lingue e la loro presenza nell'insegnamento della corrispondenza commerciale italiana - Lenassi, Nives (Linguistica (Ljubljana), 2014)
The article is based on the guidelines of the Common European Framework of Reference for Languages (CEFRL). Itpresents the results of a study aimed to determine to what extent they are taken into account in seven textbooks used for teaching business Italian. Given the importance of vocabulary in this type of language teaching, the article focuses on certain lexical and semantic aspects of business correspondence such as wordformation, synonymy, antonymy, collocations, part-whole relations, translation equivalence, and register differences. The analyses show that the authors of the materials covered these aspects well (albeit in different ways and to different extents in individual textbooks) despite the fact that in most cases the textbooks were written before the CEFRL was published or was known. In addition, two categories not present in the Framework but characteristic of business language were also recognized as important by the authors of the textbooks and presented in the task sections. These are some frequently used abbreviations and definitions (or their approximations considering the communicative language competence acquired) that learners can use to fill lexical gaps.
Keywords: besedišče; Cadre européen commun de référence pour les langues; CECRL; correspondance commerciale; Italian; italien; italijanščina; lexique; manuels; poslovna korespondenca; SEJO; semantics; semantika; sémantique; Skupni evropski jezikovni okvir; tuji jeziki; učbeniki